ChemInform Abstract: Silicon Nanocrystals and Silicon‐Polymer Hybrids: Synthesis, Surface Engineering, and Applications. Issue 13 (March 2016) - Dasog, Mita; Kehrle, Julian; Rieger, Bernhard; Veinot, Jonathan G. C.
Abstract: Review: [101 refs.